Evaluation of mechanical and thermal performance of jute and coconut fiber-reinforced epoxy composites with rice husk ash for wall insulation applications - Md. Ahtesham Akhter; Dipayan Mondal; Arup Kumar Debnath; Md. Ashraful Islam; Md. Sanaul Rabbi (Heliyon)
This study aimed to investigate the mechanical properties and thermal properties of epoxy composites reinforced jute and coconut fibers with varied rice husk ash (RHA) percentages for thermal insulation in building wall insulation. In this study, according to ASTM standards, the seven types of composite samples with varying filler ratios were prepared using the hand lay-up process. The four jute fiber (JF) samples were prepared with RHA at 0 % (control), 1 %, 2 %, and 3 % of total weight respectively, while the other three coconut fiber (CF) samples were prepared with CF at 0 % (control), 1 %, and 3 % RHA, respectively. The mechanical and thermal properties were measured for repeated three samples by using the UTM and TRSYS101 units, respectively. Regarding the mechanical characteristics, tensile strength increased with the increment of filler percentage for jute fiber composites, however, tensile strength reduced in the coconut coir composites as the filler percentage increased. The jute fiber composite sample consisting of 3 % RHA was found to be the highest among the seven composite samples, with a maximum ultimate tensile strength of 50.07 MPa and the highest tensile modulus of elasticity (2.85 GPa) with better energy absorption property. In terms of flexural strength tests, with the increase of filler percentage in coconut coir composites, the flexural properties decreased as well. On the contrary for jute fiber composites, 3 % RHA-JF composite had the highest flexural strength and moderate flexural modulus of elasticity. This study also found that with the increase of RHA percentage in JF composites, the thermal conductivity decreases, with a minimum value of 0.03697 W/m.K was found in 3 % RHA-JF composite, while in CF composites, it increased with the filler percentage. However, the combined uncertainties of mechanical properties (tensile and flexural) are estimated at 4.57 % and 4.93 %, respectively, while estimated at 5.67 % for thermal conductivity measurement. As, 3 % RHA-JF composite offers low thermal conductivity, good strength, and energy absorption, it is suitable for thermal insulation applications. Furthermore, the heat transfer analysis has been studied analytically by considering two types of wall insulation configurations (type 1 and type 2). Due to its easy capability to insert or attach inside the wall insulation and get almost similar heat transfer rate, type 2 is considered in actual practice of wall insulation. Moreover, the scope of this study is to explore agricultural waste to reduce environmental impact and enhance energy efficiency through thermal insulation inserted inside the domestic building's wall.